The impact of working capital management, debt and size on SMEs' performance: evidence from Malaysia - Ali, Isyaku (2016)
The aim of this study is to provide empirical evidence on the impact of working capital management, debt and size on SMEs' performance in Malaysia focusing on the manufacturing sector. A panel data sample of 105 firms for the study was obtained from the Companies' Commission of Malaysia (CCM) for the period from 1996 to 2015. The Generalized Least Square (GLS) was used for testing the hypotheses of the study. The regression results show that accounts receivable period, inventory holding period, debt and size are significantly related to performance, whereas accounts payable period and cash conversion cycle are insignificantly related to performance. The results also showed accounts receivable period, accounts payable period and debt to have negative relationship with performance. But the remaining independent variables have positive relationship with performance. Furthermore, the findings have important implication for financial managers and policy-makers who regulate and propose mechanisms for SMEs development.